1990
DOI: 10.1177/030089169007600501
|View full text |Cite
|
Sign up to set email alerts
|

Parental Occupation and Other Environmental Factors in the Etiology of Leukemias and Non-Hodgkin'S Lymphomas in Childhood: A Case-Control Study

Abstract: We report the results of a hospital-based, case-control study on acute lymphocytic leukemia (ALL), acute non-lymphocytic leukemia (AnLL) and non-Hodgkin lymphoma (NHL) in childhood. The study was conducted from 1981 to 1984 in Turin (Italy). One hundred and forty-two children with ALL, 22 with AnLL and 19 with NHL were included, as well as 307 controls. Information on parental smoking habits, parental occupation, ionizing radiation and childhood diseases were collected using a standard questionnaire during a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
100
1
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 20 publications
8
100
1
4
Order By: Relevance
“…However, several authors have already pointed out the possibility of a negative association with asthma and other allergic diseases (Magnani et al, 1990;Petridou et al, 1997;Schuz et al, 1999b;Wen et al, 2000), and the association deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, several authors have already pointed out the possibility of a negative association with asthma and other allergic diseases (Magnani et al, 1990;Petridou et al, 1997;Schuz et al, 1999b;Wen et al, 2000), and the association deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…392 Deliveryrelated procedures, including having a Cesarean section (OR 5 1.6, 95% CI: 1.0-2.6) or use of paracervical anesthesia (OR 5 1.8, 95% CI: 1.0-3.5), were associated positively with NHL risk in offspring. Magnani et al 680 examined the associations between parental characteristics and risk of childhood NHL. Maternal occupations that were associated with a significantly elevated relative risk of having a child with NHL included work as a high school teacher or baker/confectioner, and paternal occupations associated with NHL in offspring included work as a construction worker or lorry driver.…”
Section: Childhood Lymphomamentioning
confidence: 99%
“…Cigarette smoking has been proposed as one factor that could potentially increase the risk of NHL, although epidemiologic investigations of smoking and NHL have yielded conflicting results (Magnani et al, 1990;Brown et al, 1992;Linet et al, 1992;Tavani et al, 1994;Nelson et al, 1997;Zahm et al, 1997;Adami et al, 1998;De Stefani et al, 1998;Freedman et al, 1998;Herrinton and Friedman, 1998;Holly et al, 1999;Miligi et al, 1999;Grant, 2000;Parker et al, 2000;Fabbro-Peray et al, 2001;Peach and Barnett, 2001;Stagnaro et al, 2001;Besson et al, 2003). Three studies have reported a statistically significant increased risk of NHL among smokers (Magnani et al, 1990;Linet et al, 1992;Freedman et al, 1998), while eight studies have reported no association or a weak association between cigarette smoking and NHL (Tavani et al, 1994;Nelson et al, 1997;Adami et al, 1998;De Stefani et al, 1998;Holly et al, 1999;Miligi et al, 1999;Grant, 2000;Fabbro-Peray et al, 2001).…”
mentioning
confidence: 99%
“…Three studies have reported a statistically significant increased risk of NHL among smokers (Magnani et al, 1990;Linet et al, 1992;Freedman et al, 1998), while eight studies have reported no association or a weak association between cigarette smoking and NHL (Tavani et al, 1994;Nelson et al, 1997;Adami et al, 1998;De Stefani et al, 1998;Holly et al, 1999;Miligi et al, 1999;Grant, 2000;Fabbro-Peray et al, 2001).…”
mentioning
confidence: 99%